STUDI ANALISIS STABILITAS LERENG DENGAN PERKUATAN SOIL NAILING MENGGUNAKAN PROGRAM GEOSLOPE - Nofrizal, Nofrizal; Ronaldo, Ronaldo; Febrian, Deo; Zakiah Ariani, Rahima (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Cantilever type retaining walls are a type of retaining wall which is often used to withstand quite extreme ground movements in areas with fairly high steep slopes. Cantilever type earth retaining walls are made of reinforced concrete consisting of vertical walls and base plates or footings with T-shaped reinforcement. The thickness of both parts of the structure is usually relatively thin and is reinforced thoroughly at a distance determined based on reinforcement calculations to withstand moments and latitude force acting on the wall. To carry out work on the retaining wall, previously the base of the slope is excavated as the base of the retaining wall, then using formwork or molds that have been arranged with reinforcement and then cast with concrete. The aim of preparing this final assignment is to determine the stability of existing slopes using Geo-slope and the Fellenius method. And finding the safe figure (SF) on the slope due to the working loads has been strengthened by strengthening the cantilever type tiered retaining wall. Planning effective and efficient dimensions for a cantilever type tiered retaining wall to overcome the problem of slope failure at the research location. From the research, it was concluded that the Factor of Safety (FoS) value of the slope using simulation using Geoslope/W 2012 software was 0.318. From the results obtained it can be said that the slopes of the research area are unsafe because the Factor of Safety (FoS) value is less than <1. Simulations using several variations of angles 30 ̊ , 45 ̊ 60 ̊ and 75 ̊ without reinforcement obtained minimum and maximum Factor of Safety (FoS) values of less than 1. Thus, slope stability using several variations of angles is unsafe. Key words: slope, landslide, factor of safety